2020
DOI: 10.3390/cells9112355
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Acid-Sensing Ion Channel 3 Relieves the Late Phase of Neuropathic Pain by Preventing Neuron Degeneration and Promoting Neuron Repair

Abstract: Neuropathic pain is one type of chronic pain that occurs as a result of a lesion or disease to the somatosensory nervous system. Chronic excessive inflammatory response after nerve injury may contribute to the maintenance of persistent pain. Although the role of inflammatory mediators and cytokines in mediating allodynia and hyperalgesia has been extensively studied, the detailed mechanisms of persistent pain or whether the interactions between neurons, glia and immune cells are essential for maintenance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The alteration of DRG neurons after nerve injury have been approached in previous research. After nerve injury, both large‐ and small‐diameter neurons are partially damaged and lost, and the contributions of large and small neurons are time‐dependent (Kung et al, 2020; Leibovich et al, 2020). The expression of different sub‐populations in small‐diameter neurons (i.e., peptidergic and nonpeptidergic neurons) in DRGs also changed after nerve injury (Yeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of DRG neurons after nerve injury have been approached in previous research. After nerve injury, both large‐ and small‐diameter neurons are partially damaged and lost, and the contributions of large and small neurons are time‐dependent (Kung et al, 2020; Leibovich et al, 2020). The expression of different sub‐populations in small‐diameter neurons (i.e., peptidergic and nonpeptidergic neurons) in DRGs also changed after nerve injury (Yeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in ASIC3 −/− mice, a marked reduction in acid-induced pain was noticed, along with a decrease in the ability to prime nociceptors [ 136 ]. Moreover, ASIC3 −/− mice were unable to develop chronic muscle pain, establishing a clear correlation between ASIC3 and nociception [ 137 ]. In mouse DRG neurons, recent experiments have shown that ASIC3 expresses the dual function of mechanosensation and acid-sensation [ 138 ].…”
Section: Asics In Mechanosensationmentioning
confidence: 99%
“…Despite some of these promising findings, we deem it unlikely that any of these small molecule modulators will prove successful in targeting ASIC-related pain phenotypes due to their lack of specificity. APETx2, rat, IM or IT ~Mechanical sensitivity of paw (FF) [67] RPRFa peptide, mouse, IM ↑ Mechanical sensitivity of paw (FF) ~Mechanical sensitivity of paw (FF) in ASIC3 KO [56] Nociceptive pain via formalin, paw NS383 or Amiloride, rat, IP ↓ Nocifensive flinching behaviors [35] Mambalgin, mouse, IT ↓ Spontaneous pain behaviors [50] PPC-5650, rat, SC ↓ Nocifensive licking behavior [51] Inflammatory hyperalgesia induced by CFA injection into paw Amiloride or A-317567, rat, IP ↓ Thermal sensitivity of paw [38] PcTx1, rat, paw ↓ Inflammation score of paw [47,48] APETx2, rat, paw ↓ Mechanical sensitivity of paw (pinch) [65,67] APETx2, rat, IT ~Mechanical sensitivity of paw (pinch) [67] NS383 or Amiloride, rat, IP ↓ Weight bearing distribution ~Thermal sensitivity of tail Neuropathic pain via CCI NS383 or Amiloride, rat, IP ↓ Mechanical sensitivity of paw (FF) [35] Mambalgin, mouse, IV ↓ Thermal sensitivity of paw ↓ Thermal sensitivity of paw in ASIC1a KO ↓ Mechanical sensitivity of paw (FF) [49] Mambalgin, mouse, IT ↓ Thermal sensitivity of paw ~Thermal sensitivity of paw in ASIC1a KO [49] No treatment, mouse ↓ Mechanical sensitivity of paw (FF) in ASIC3 KO ↓ Thermal sensitivity of paw in ASIC3 KO [58] APETx2, mouse, IT ↓ Mechanical sensitivity of paw (FF) ↓ Thermal sensitivity of paw [58] Osteoarthritis pain via MIA injection into knee Acetylsalicylic acid, rat, oral ↓ Mechanical sensitivity of paw (FF) [43] Compound 10b, rat, IP Better weight bearing distribution ↓ Mechanical sensitivity of paw (FF) [62] Orthodontic force GMQ, rat, periodontal Acidic saline, rat, periodontal ↓ Bite force [60] APETx2, rat, periodontal ↑ Bite force…”
Section: Inhibition Across Different Asic Subtypesmentioning
confidence: 99%
“…In rodents, ASIC3 is predominantly expressed in the PNS and is the most prevalent ASIC isoform in the dorsal root ganglion (DRG) [54]. Numerous in vivo studies therefore focus on its involvement in osteoarthritic pain induced by injection of monosodium iodoacetate (MIA) into the knee [43,62]; neuropathic pain induced by chronic constriction injury of the sciatic nerve [39,49,58]; gastroesophageal reflux disease (GERD), and irritable bowel syndrome (IBS) simulated by local mechanical, thermal, and electrical stimuli via a rectal or esophageal probe, respectively [52,53]; migraine induced either by IP injection of isosorbide dinitrate (ISDN) or nitroglycerine (NTG), or cannulated infusion of inflammatory soup [39,64,68]; inflammatory pain induced by injection of Complete Freund's Adjuvant (CFA), acidic saline, or carrageenan into the gastrocnemius muscle or hind paw [35,38,39,44,[47][48][49][50][51]56,59,62,63,[65][66][67]70,71,100,102]; acid-induced pain through local injection or iontophoresis [36,37,44,66,100,101]. (B) selection of different paradigms to assess pain sensitivity [35][36][37][38]…”
Section: Targeting Asic3mentioning
confidence: 99%
See 1 more Smart Citation